Praktik Inisiasi Menyusu Dini - Etisa Adi Murbawani; Etika Ratna Noer (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2011)
Early initiation of breastfeeding (EIB) and exclusive breastfeeding (EB) up to six months are two important breastfeeding practices for child’s survival. EIB plays an important role in reducing infant mortality and improve the success of exclusive breastfeeding. This study aimed to investigate determinant factors in EIB. The subjects were mothers who gave birth in 2 health centers in the Semarang city. This study used a qualitative approach. Data were collected through intensive observations, non-intervention and in-depth interviews. Data analyzed by content analysis include data collection, data reduction, data presentation, and conclusions. All the mothers (12 subjects) successful in the EIB with the help of professional midwife (reinforcing factors). The influence of enabling factors (health policy ) and reinforcing factors (midwife) ensure practice of EIB.